Penerapan Pasal 22 Undang-Undang Nomor 23 Tahun 2011 Tentang Pengelolaan Zakat Pada Koperasi Serba Usaha Bina Utama Makassar - Pratiwi AM, Memi; Nurfaidah, Annisa; Alifuddin, Moh (STMIK Amika Soppeng, 2024)
The study aims to see whether the application of Article 22 of Law Number 23 of 2011 concerning Zakat Management in the Makassar Bina Utama Multipurpose Cooperative has been applied to employees. The method used is qualitative with an inductive approach with primary data and secondary data. Furthermore, the data collection methods used were observation and interviews. After the data was collected, data management techniques were carried out in three stages, namely: data reduction, data presentation, and drawing conclusions. The results of the research show that the application of zakat as a deduction from Taxable Income at the Bina Utama Makassar Multipurpose Cooperative provides additional knowledge to all employees to pay zakat and taxes and increases public awareness and honesty in paying zakat, this has had a good impact on state income. Based on the research results, the researcher's suggestion is that the Bina Utama Makassar Multipurpose Cooperative hopes that wider socialization of zakat and taxes, both personal and corporate, can reduce the double burden.